Influence of tannin-rich pine bark supplementation in the grain mixes for meat goats: Growth performance, blood metabolites, and carcass characteristics - Desnatie Reynolds; Byeng Ryel Min; Nar Gurung; Wendell McElhenney; Jung Hoon Lee; Sandra Solaiman; Olga Bolden-Tiller (Animal Nutrition, 2020)
The objective was to evaluate the use of condensed tannin (CT)-rich ground pine bark (PB) in grain mixed diets on meat goat growth performance, blood metabolites, and carcass characteristics. Twenty four Kiko crossbred (Capra aegagrus hircus) growing male kids (BW = 36.9 ± 2.5 kg) at approximately 8 months of age were assigned randomly to 2 treatments with 3 replicates per treatment and 4 goats per replicate. The goats were fed grain mixed diets composed of either 30% bermudagrass hay (BGH) plus concentrate (control) or 30% PB plus concentrate. Diets were fed at 1.2% of BW. In addition, all goats grazed a crabgrass/bermudagrass (CB)-based pasture. The feeding trial lasted for 55 d. Using ground PB as a supplement did not negatively affect BW, average daily gain (ADG), carcass characteristics, meat pH, and meat color compared to the control diet. Plasma gamma-glutamyl transferase (P = 0.03), glucose (P < 0.01) and Ca concentrations (P = 0.04) were higher for PB than for BGH, respectively. The 30% PB supplementation does not negatively affect animal performance, blood metabolites, and carcass parameters. Keywords: Pine bark, Goats, Animal performance, Blood metabolites, Carcass traits